Optimization Design and Test Analysis of Rice Electric Binder Knotter Based on ADAMS - Difa Bao; Jufei Wang; Zhi Liang; Chongcheng Chen; Wuxiong Weng; Shuhe Zheng; Jinbo Ren (Agriculture)
The knotter, as a core module for the knotting function of a rice electric binder, has structural parameters and spatial configurations that significantly impact the efficiency and quality of rice collection, making the in-depth analysis and optimization of these parameters, and their spatial relationships, crucial for enhancing the operational quality of the rice electric binder. At present, rice binders still face the issues of a low bundling efficiency and quality, which affect the progress of rice harvesting during the harvest season. Through theoretical analysis and calculation, this study determined the main parameters affecting the knotter’s knotting process and their value ranges. Based on the ADAMS software, a simulation model of the knotter operation was constructed. Using the Box–Behnken design (BBD) method and response surface analysis of variance, a regression prediction model for knotter operation evaluation indicators was established, and the multi-objective optimization of the knotter’s operation quality was performed. The prediction results showed that, under the optimal structural parameter combination of a 30.23° angle between the knotting pincer and rope guard axes, a −3.75 mm rope clamping board position, and a 40.75° inclination angle of the knotting pincer convex platform, the knotter’s knotting quality reached the best state, with an average knot end protrusion of 9.10 mm and a maximum tension of 134.25 N on the knotting rope. The field tests results showed an average knot end protrusion of 9.60 mm and a maximum tension of 127.87 N on the knotting rope, with average relative errors of 5.82% and 4.72% compared to the theoretical values, respectively. After optimizing the knotter, the average knot end protrusion increased by 14.48% and the maximum tension of the knot rope was reduced by 11.27%. Meanwhile, the knotter achieved an average bundling rate as high as 99.3%. The bundling success rate also increased by 2.7%. These results fully verify the reliability and accuracy of the regression model, and demonstrate the reasonableness of the knotter structural parameter optimization design, providing a theoretical basis and reference for improving the operational quality of the rice electric binder.